A g-C3N4/MIL-101(Fe) heterostructure composite for highly efficient BPA degradation with persulfate under visible light irradiation. Issue 46 (14th November 2018) - Gong, Yan; Yang, Bo; Zhang, Hui; Zhao, Xu
Abstract : Heterostructured composites with outstanding photocatalytic performance have attracted intense attention because of their great potential for use in environmental remediation. Abstract : Heterostructured composites with outstanding photocatalytic performance have attracted intense attention because of their great potential for use in environmental remediation. Herein, a facile hydrothermal method to obtain heterostructured composites consisting of graphitic-carbon nitride (g-C3 N4 ) and an Fe-based metal organic framework (MIL-101(Fe)) is reported. The as-prepared hybrids exhibited dramatically improved photocatalytic performance for bisphenol A (BPA) degradation in the presence of persulfate (PS) under visible light irradiation. The apparent rate constant, k, for BPA degradation by g-C3 N4 /MIL-101(Fe) composites with PS was approximately 8.9 times higher than that obtained with bare g-C3 N4 . The superior performance arises from the heterojunction formed between MIL-101(Fe) and g-C3 N4 with a favourable band position and the excellent PS activation ability of MIL-101(Fe), which not only enables the fast electron transfer from g-C3 N4 to MIL-101(Fe) but also accelerates PS activation for SO4 ˙ − radical production. This work provides an effective way for constructing novel photocatalytic systems with efficient activity for refractory pollutant removal.